2012
DOI: 10.1002/jcb.24090
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2 overexpression confers oncogenic potential to human lung cancer cells by deregulating expression of apoptosis and cell cycle proteins

Abstract: Histone deacetylase 2 (HDAC2) is crucial for embryonic development, affects cytokine signaling relevant for immune responses, and is often significantly overexpressed in solid tumors, but little is known of its role in human lung cancer. In this study, we demonstrated the aberrant expression of HDAC2 in lung cancer tissues and investigated oncogenic properties of HDAC2 in human lung cancer cell lines. HDAC2 inactivation resulted in regression of tumor cell growth and activation of cellular apoptosis via p53 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 24 publications
3
64
0
2
Order By: Relevance
“…Previous researches showed that HDACs including HDAC 2 are associated with the stability of proteins that regulate cell cycle, including some cyclins such as cyclin A/E/D1, CDKs like CDK2 and other cell cycle associated components. Thus it could regulate cancer cell growth arrest and apoptosis, and agents that regulate HDAC 2 could exhibit anticancer activities [43][44][45]. So we suggest that HDAC, especially HDAC 2, may be the direct target of SKLB316.…”
Section: Discussionmentioning
confidence: 96%
“…Previous researches showed that HDACs including HDAC 2 are associated with the stability of proteins that regulate cell cycle, including some cyclins such as cyclin A/E/D1, CDKs like CDK2 and other cell cycle associated components. Thus it could regulate cancer cell growth arrest and apoptosis, and agents that regulate HDAC 2 could exhibit anticancer activities [43][44][45]. So we suggest that HDAC, especially HDAC 2, may be the direct target of SKLB316.…”
Section: Discussionmentioning
confidence: 96%
“…COPD has been shown to increase the risk for developing lung cancer (143). Overexpression of HDAC2 confers oncogenic potential to human lung cancer cells (49). Thus further study is required to resolve this controversy by differentiating HDAC2 regulation and its dependent epigenetic changes in senescence during the development of COPD and lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Valproic acid and TSA affect acetylation status of p53 and induce apoptosis in ERG-positive prostate cancer cells (26). In human lung cancer cell lines, HDAC inactivation results in the induction of apoptosis via p53 and Bax activation (27). P27, which inhibits CDK4-and CDK2-containing complexes, was induced by vorinostat and/or TSA, in leukemia cells (28) and breast cancer cells (29).…”
Section: Discussionmentioning
confidence: 99%